The Predictors of Indonesia’ Patient’s Loyalty a Literature Review - Tiara Turay (Universitas Dharma Andalas, 2022)
The purpose of this study is to determine the factors that predict Indonesia’s patient’s loyalty. The methodology of this research is conceptual paper that review several literatures from past studies regarding the factors that determine patient’s loyalty. After reviewing the literature extensively, it found that healthcare service quality, hospital reputation, and patient’s confidence are included as the predictor of Indonesia’s patients Loyalty. It is highly recommended for Indonesia’s healthcare providers to deliver adequate healthcare service quality to boost hospital reputation and patients’ confidence to build patient loyalty. At the end, the researcher extensively discussed the findings, implications, and the limitations of the study, and equally made recommendations for future research to broaden the scope of the research in terms of the variables, population, and methodology